2019
DOI: 10.1016/j.ijfatigue.2019.02.014
|View full text |Cite
|
Sign up to set email alerts
|

Numerical modelling of surface roughness effect on the fatigue behavior of Ti-6Al-4V obtained by additive manufacturing

Abstract: Selective Laser Melting (SLM) is a powder bed fusion process which allows to build-up parts by successive addition of layers using 3D-CAD models. Among the advantages, the high degree of freedom for part design and the small loss of material explain the increasing number of Ti-6Al-4V parts obtained by this process. However, right after additive manufacturing, these parts contain defects (surface roughness, porosity, residual stresses) which significantly decrease the High Cycle Fatigue (HCF) life. In order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
49
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 125 publications
(60 citation statements)
references
References 38 publications
1
49
0
1
Order By: Relevance
“…Regarding the effect of the as built surface on the fatigue behaviour, numerous studies [8][9][10][11][12] have shown that the as built surface is detrimental to the fatigue strength. Several approaches have been developed in the literature to model the effect of surface roughness defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the effect of the as built surface on the fatigue behaviour, numerous studies [8][9][10][11][12] have shown that the as built surface is detrimental to the fatigue strength. Several approaches have been developed in the literature to model the effect of surface roughness defects.…”
Section: Introductionmentioning
confidence: 99%
“…Vayssette el al. [8] tried to estimate the fatigue strength via numerical simulations by using the finite element method and achieved satisfactory predictions. In the work of Nakatani et al [11], the classical Murakami approach is used in which the surface roughness defect size is measured by using the √ area parameter.…”
Section: Introductionmentioning
confidence: 99%
“…They significantly influence the static and dynamic mechanical properties of a material including fatigue strength. Several studies have been carried out recently to assess the fatigue behavior of different AM materials, that is, AlSi10Mg [9][10][11][12], Ti6Al4V [13][14][15][16][17][18], Ni-based alloy [19], 15-5 PH stainless steel [20], steel [21], stainless steel [22]. Nasab et al [23] studied the effect of surface and subsurface defects on the fatigue behavior of AlSi10Mg.…”
Section: Introductionmentioning
confidence: 99%
“…(3) Modelling the material with the geometrical defects, usually by means of finite element software. This method can be done based on, eg , computed tomography 3D image or surface profile from a confocal microscope, obtaining the geometry, then importing it as a 3D model into a finite element software and applying loads …”
mentioning
confidence: 99%